The challenges in the capture and storage of digital information by rural clinics in Hammarsdale, KwaZulu-Natal Province - Mchunu, Mbali (Department of Knowledge and Information Stewardship, 2025)
The study examined the capture and storage of patient information by rural health care clinics in Hammarsdale in KwaZulu-Natal. The study was supported by the Digital Curation Centre Life Cycle model and the primary aim of the study was to identify the nature and scale of the challenges faced in the capture and storage of patient medical records. A mixed-method approach was adopted to the collection of data that was relevant to addressing the research objectives. The study used convenience, self-selection, and expert sampling to select participants for the questionnaires and interviews. Interviews were carried out with selected staff in the records office at the clinics with a target sample of at least one staff in each clinic. Data collection methods included interviews and questionnaires. Triangulation was also adopted for crosssectional analysis of the data collected. The study revealed that the rural clinics operated a duplicate system for the capture and storage of patient medical information. Furthermore, the systems did not complement each other as both the paper and electronic records systems had their own weaknesses. However, the use of the paper records systems was predominant. The conclusion from the findings was that there was a need to institute policy measures to guide the capture and storage of patient medical records. The recommendations are that the DCC Life Cycle can be used as a guide in developing policies and guidelines on how both paper and electronic records can be captured and stored.